Factors Contributing to Identity Confusion in Adolescents from Immigrant Families - Bennett, Laura; Moreau, Samuel; Matthews, Brian. (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to explore the key factors contributing to identity confusion in adolescents from immigrant families living in Canada. Methods and Materials: A qualitative research design was used with a phenomenological approach to capture the lived experiences of adolescents navigating identity challenges in the context of immigration. A purposive sample of 31 second-generation immigrant adolescents aged 13 to 18 years was recruited from various provinces in Canada. Data were collected through semi-structured interviews focused on cultural conflict, family dynamics, social experiences, and emotional well-being. Interviews continued until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed thematically using NVivo software. Braun and Clarke’s six-phase thematic analysis method guided the coding and theme development. Findings: Five main categories emerged from the analysis: cultural dissonance, social belonging and exclusion, family expectations and role strain, emotional turmoil and psychological strain, and navigating self and future. Each category contained several subcategories, such as conflicting cultural norms, peer rejection, academic pressure, emotional suppression, and self-acceptance. Participants reported a fragmented sense of self due to cultural contradictions, intergenerational conflicts, and perceived discrimination. Many described feelings of shame, anxiety, and confusion, while others expressed resilience and pride in bicultural identities. The study highlights the role of family communication, peer inclusion, and personal agency in shaping identity development. Conclusion: Identity confusion among adolescents from immigrant families is a complex, multifaceted phenomenon shaped by intersecting cultural, familial, and emotional experiences. While it presents psychological risks, it also offers opportunities for self-exploration and identity integration when supported by inclusive environments and open communication.